'Hijacking' core metabolism: a new panache for the evolution of steroidal glycoalkaloids structural diversity. (June 2020) - Sonawane, Prashant D.; Jozwiak, Adam; Panda, Sayantan; Aharoni, Asaph
Abstract : Steroidal glycoalkaloids (SGAs) are defense specialized metabolites produced by thousands of Solanum species. These metabolites are remarkable in structural diversity formed following modifications in their core scaffold. In recent years, it became clear that a large portion of this chemical repertoire was acquired through various molecular mechanisms involving 'hijacking' of core metabolism enzymes. This was typically accompanied by gene duplication and divergence and further neofunctionalization as well as modified subcellular localization and evolution of new substrate preferences. In this review, we highlight recent findings in the SGAs biosynthetic pathway and elaborate on similar occurrences in other chemical classes that enabled evolution of specialized metabolic pathways and its underlying structural diversity.